Beta vulgaris production with micronutrient fertigation of seedlings - Cunha, Pedro Henrique Hortolani [UNESP]; de Sá, Jolinda Mércia [UNESP]; Cardoso, Antonio Ismael Inácio [UNESP] (Universidade Estadual Paulista - Campus de Tupa, 2024)
Adequate seedling nutrition is essential for beet production. This study evaluated the effects of applying boron, molybdenum, nitrogen and zinc to seedlings, considering agronomic characteristics and productivity. The experiment was carried out at the São Manuel Experimental Farm of the São Paulo State University, with a randomized block design, seven treatments (fertilizers) and five replicates: T1-control (without application), T2-Raiz® (4% N, 5% Mo), T3-‘Raiz®+Zintrac®’, T4-Biotrac® (5.6% N, 2.3% K2O, 1.1% B, 1,1% Zn), T5-‘Biotrac®+Zintrac®’, T6-Zintrac® (1% N, 40% Zn) e T7-‘Raiz®+Biotrac®’. Doses of 2.0 mL/L for Biotrac® and 0.5 mL/L for Raiz® and Zintrac® were used. The cultivar used was Betana from Feltrin Sementes®, sown in 200-cell trays. The applications took place 8 days after emergence. Evaluations at transplanting and at the end of the cycle included length, diameter, number of leaves and fresh and dry mass of seedlings and adult plants. Treatment T3 (Raiz® + Zintrac®) showed the highest fresh root mass (120 mg). The combination of Raiz® with Zintrac® and Biotrac® increased the number of leaves (3.6) and fresh root mass (20 mg) compared to the control. The application of Biotrac® alone (T4) resulted in the highest root yields (6.25 and 5.50 t/ha), the largest root diameter (19.68 cm) and the highest fresh leaf mass (125 mg). The Zintrac® (T6) treatment resulted in a higher fresh leaf mass (112.8 mg) than the control. However, the results were below commercial expectations.
Keywords: Beet; Boron; Molybdenum; Nitrogen; Zinc